Complexities in Drafting Land Transfer Deeds After the Implementation of Electronic Land Certificates : (A Study of Land Deed Officials in Bekasi) - Harsanti, Khairunnisa Putri; Taupiqurrahman, Taupiqurrahman (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
Land registration aims to ensure legal certainty and protection of land rights through the issuance of certificates. Along with technological developments, the Indonesian government has implemented electronic land certificates to improve efficiency in land administration. Nevertheless, this transition has generated new complexities for Land Deed Officials (PPAT) in drafting land transfer deeds. This study aims to analyze the complexity that arises in drafting land transfer deeds after the implementation of electronic land certificates, and how PPATs respond to these challenges in practice. The methodology employed is an empirical juridical approach; this research is based on interviews with PPATs in Bekasi City. The findings indicate that electronic certificates present significant challenges in ensuring the accuracy of both legal subjects and objects in land transfer deeds, primarily due to data limitations and inconsistencies. These complexities hinder PPATs in fulfilling their responsibilities to guarantee legal validity and certainty. The study concludes that the current implementation of electronic certificates has not yet fully achieved its intended objective of legal certainty, thereby underscoring the need for stronger data integration and institutional coordination to support a reliable and accountable land transfer process.